KEANEKARAGAMAN FAUNA IKAN EKOSISTEM MANGROVE DIKAWASAN TAMAN NASIONAL UJUNG KULON, PANDEGLANG-JAWA BARAT - Wahyudewantoro, Gema (BERITA BIOLOGI, 2009)
Fish fauna survey biodiversity was conducted in Ujung Kulon National Park, Pandeglang-West Java, to reveal fish diversity in mangrove ecosystem. Samples were caught using electrofish (12 V 10A), gill net (mesh sized 1-1.5cm) and fishing tackle.Result showed that there were 58 fish species belongs to 34 families and 43 genera Gobiidae was a dominant famili with 8 spesies, followed by Apogonidae, Chandidae, Lutjanidae and Serranidae each with 3 species. Cigenter river has highest diversity with H = 2.74, E=0.930, d = 5.346. Serinding fish (Ambassis dussumieri) was the highest abundance compared to others.